Nature of Simple Proof as a Condition for Application for Postponement of Debt Payment Obligations and Bankruptcy Against Developers (developers) of Apartments and / or Flats After Supreme Court Circular Letter Number 3 of 2023 - Andrew Ardiyanto Dachlan; Ariyanto Hermawan; Hilmy Syaiful Rachmansyah; Agus Apria Widodo; Ivan Ilham Kusuma (Journal of Law, Politic and Humanities, 2024)
The issuance of Supreme Court Circular Letter (SEMA) Number 3 of 2023 concerning the Implementation of the Formulation of the Results of the Plenary Meeting of the Supreme Court Chamber in 2023 as Guidelines for the Implementation of Duties for the Courts, raises legal problems when correlated with the provisions on the principle of simple proof as a condition for postponement of debt payment obligations and bankruptcy as stipulated in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations Article 8 paragraph (4). This paper uses normative legal research method with statutory approach and conceptual approach. The results of the research show that the SEMA in question is not a product of legislation and has implications that are not binding in general, only applies to the internal environment of the Supreme Court, but the consequences of the circular letter are guidelines for judges to be able to reject bankruptcy applications and postponement of debt payment obligations against developers (developers) of apartments, flats.